Study on Strategy of IMS Cloud - Lin Wu; Lei Shen; Zhanyue Xi (Dianxin kexue)
The cloud computing is surging and its applications have penetrated in all sectors, including the telecommunications industry. As unified core control of the future convergence of fixed and mobile networks, the importance of IMS network is becoming more prominent. The study on IMS cloud has been just started. The driving force of IMS cloud was introduced firstly, then described the IMS cloud from the aspects of concept, position in the layered cloud reference model and deployment model were described, the overall IMS cloud architecture and strategies were proposed, finally the changes it bring to the operators were briefly analyzed.